Pengaruh Efek Carpooling Niat Pembelian pada Calon Pembeli Mobil Bekas di Indonesia - Dhevia Halimah Ramadhani; Ida Bagus Nyoman Udayana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to explore the relationship and direct influence of Cognitive Capital and Social Interaction on Information/knowledge sharing behavior, the effect of Information/knowledge sharing behavior on purchase intention, and the direct influence of cognitive capital and social interaction on customer purchase intention on prospective used car buyers in Indonesia. On an ongoing basis, the company improves the behavior of sharing information/knowledge to bind customers so that there is customer buying interest in a product. Purchase intention is one of the important things in a company, if a company occurs in the behavior of sharing information/knowledge to customers, the customer's interest in buying a product will also increase. These efforts can be realized in the form of increasing customer cognitive capital, increasing social interaction with customers, and being able to provide better service to customers. Data were collected as many as 60 used car buyers with data collection techniques using a questionnaire containing 20 questions that must be filled out. The data that has been collected is then processed with SPSS for validity testing, hypothesis testing and classical assumption testing. The results showed that the cognitive capital variable had a positive effect on information/knowledge sharing behavior, social interaction had a positive effect on information/knowledge sharing behavior, and information/knowledge sharing behavior had a positive effect on purchase intention. Keywords: influence of purchasing decisions, purchase intentions